A Difference in Fatty Acid Composition of Isocaloric High-Fat Diets Alters Metabolic Flexibility in Male C57BL/6JOlaHsd Mice - Duivenvoorde, Loes P M; van Schothorst, Evert M; Swarts, Hans M; Kuda, Ondrej; Steenbergh, Esther; Termeulen, Sander; Kopecky, Jan; Keijer, Jaap (PLoS One, 2015)
Poly-unsaturated fatty acids (PUFAs) are considered to be healthier than saturated fatty acids (SFAs), but others postulate that especially the ratio of omega-6 to omega-3 PUFAs (n6/n3 ratio) determines health. Health can be determined with biomarkers, but functional health status is likely better reflected by challenge tests that assess metabolic flexibility. The aim of this study was to determine the effect of high-fat diets with different fatty acid compositions, but similar n6/n3 ratio, on metabolic flexibility. Therefore, adult male mice received isocaloric high-fat diets with either predominantly PUFAs (HFpu diet) or predominantly SFAs (HFs diet) but similar n6/n3 ratio for six months, during and after which several biomarkers for health were measured. Metabolic flexibility was assessed by the response to an oral glucose tolerance test, a fasting and re-feeding test and an oxygen restriction test (OxR; normobaric hypoxia). The latter two are non-invasive, indirect calorimetry-based tests that measure the adaptive capacity of the body as a whole. We found that the HFs diet, compared to the HFpu diet, increased mean adipocyte size, liver damage, and ectopic lipid storage in liver and muscle; although, we did not find differences in body weight, total adiposity, adipose tissue health, serum adipokines, whole body energy balance, or circadian rhythm between HFs and HFpu mice. HFs mice were, furthermore, less flexible in their response to both fasting- re-feeding and OxR, while glucose tolerance was indistinguishable. To conclude, the HFs versus the HFpu diet increased ectopic fat storage, liver damage, and mean adipocyte size and reduced metabolic flexibility in male mice. This study underscores the physiological relevance of indirect calorimetry-based challenge tests.
Keywords: Mitochondria; játra; metabolismus lipidů; tuková tkáň; Mice, Transgenic; Lipid Metabolism; Diet, High-Fat; myši transgenní; Hypoxia; mitochondrie; zvířata; omega-3 mastné kyseliny; myši; Fatty Acids, Omega-3; Glucose Tolerance Test; myši inbrední C57BL; kyseliny mastné omega-6; Mice; Adiposity; hypoxie; Adipocytes; glukózový toleranční test; kosterní svaly; Energy Metabolism; tukové buňky; Liver; energetický metabolismus; Male; Muscle, Skeletal; Mice, Inbred C57BL; dieta s vysokým obsahem tuků; Animals; Fatty Acids, Omega-6; mužské pohlaví; adipozita; Adipose Tissue